Introduction to discourse studies - Renkema, J., 1948-; Schubert, Christoph, 1971- (John Benjamins Publishing Company, 2018)
"This new edition of Introduction to Discourse Studies (IDS) is a thoroughly revised and updated version of this successful textbook, which has been published in four languages and has become a must-read for anyone interested in the analysis of texts and discourses. Supported by an international advisory board of 14 leading experts, it deals with all main subdomains in discourse studies, from pragmatics to cognitive linguistics, from critical discourse analysis to stylistics, and many more. The book approaches major issues in this field from the Anglo-American and European as well as the Asian traditions. It provides an 'academic toolkit' for future courses on discourse studies and serves as a stepping stone to the independent study of professional literature. The chapters are subdivided in modular sections that can be studied separately. The pedagogical objectives are further supported by - over 500 index entries covering frequently used concepts that are accurately defined with examples throughout the text; - more than 150 test-yourself questions, all elaborately answered, which are ideal for self-study; - nearly 100 assignments that provide ample material for lecturers to focus on specific topics in their courses"--Resumé vydavatele